Association between regular aerobic exercise and hyperhomocysteine in hypertensive patients. Issue 5 (3rd July 2020) - Wang, Wei; Li, Jing; Ji, Peng; Bian, Rongwen; Xiong, Yaqing
ABSTRACT: Objective: The relationship between total plasma homocysteine (tHcy) and exercise remains controversial. This study aimed to investigate the association between regular aerobic exercise and hyperhomocysteine (hHcy) in patients with hypertension. Methods: A total of 497 hypertensive patients from 7 communities of Nanjing were enrolled in this cross-sectional study. All participants were asked to complete standard questionnaires by themselves. Physical and laboratory examination were performed within 1 week after enrollment. The association between regular aerobic exercise and hHcy in hypertensive patients was estimated by a multiple logistic regression analysis. Results: Of the 497 patients, 210 had a regular aerobic exercise habit and 274 of them were detected with hHcy. Multivariate analysis revealed that exercisers have less risk of hHcy (adjusted odds ratio [OR] 0.42, 95% confidence interval [CI] 0.26–0.66) as compared to non-exercisers controlling for the established and potential confounders. Intensity, frequency, and total energy expenditure of aerobic exercise were found to be independently associated with lower hHcy risk in hypertensive patients. Gender subgroup analyses showed that this inverse relationship between regular aerobic exercise and hHcy exists in both male and female groups (adjusted OR 0.41 95%CI 0.21–0.80, and adjusted OR 0.40 95%CI 0.20–0.80, respectively). Conclusions: Regular aerobic exercise has a negative association with hHcy in this cross-sectional study. That suggests a hypothesis that doing aerobic exercise might decrease the risk of hHcy in hypertensive patients.